Quantum Learning Boosts Higher-Order Thinking: Enhancing Critical Thinking and Written Argumentation in Secondary Physics - David, Andrew; Eguta, Kaia; Gargar, Kim A (Cahaya Ilmu Cendekia Publisher, 2026)
Learning method on critical thinking skills and written argumentation skills of high school students simultaneously in physics learning, to determine whether this student-centered approach is effective in improving higher-order thinking skills in secondary education. Methodology: This study employed a quasi-experimental non-equivalent control group pretest–posttest design at Kandrian Secondary School. Purposive sampling was used to select 60 eleventh-grade students divided into experimental and control groups. Instruments included essay tests based on Facione’s Delphi Report and Toulmin’s Argumentation Pattern (TAP), assessed using analytic rubrics. Data were analyzed using SPSS through N-gain, Kolmogorov–Smirnov, Levene’s Test, independent and paired samples t-tests, and Cohen’s d. Main Findings: The experimental group demonstrated significantly higher improvements in critical thinking and written argumentation skills compared to the control group. N-gain scores were in the moderate category for the experimental class and low for the control class. Independent samples t-test results showed significant differences (p < 0.05), while paired samples t-tests confirmed significant pretest–posttest gains. Cohen’s d indicated a large effect size of Quantum Learning on both competencies. Novelty/Originality of this study: This study is novel in empirically examining the simultaneous impact of Quantum Learning on both critical thinking and written argumentation skills at the senior high school level. It integrates cognitive and argumentative competencies within a single instructional intervention, advancing existing knowledge by providing combined evidence of effectiveness in a resource-limited secondary education context.